Comparison of Chemistry Learning Outcomes with Inquiry Learning Model and Learning Cycle 5E in Material Solubility and Solubility Multiplication Results - Nur Indah Firdausi (Pascasarjana Universitas Negeri Malang (UM), 2014)
Perbandingan Hasil Belajar Kimia dengan Model Pembelajaran Inquiry dan Learning Cycle 5E pada Materi Kelarutan dan Hasil Kali Kelarutan Abstract: This research is aimed to compare the effectiveness between inquiry and LC 5E in solubility equilibria and the solubility product for students with different prior knowledge. The effectiveness of both learning models is measured from students learning outcome. This quasi experimental research uses factorial2x2 with posttest only design. Research samples are chosen using cluster random sampling. They are two classes of XI IPA SMAN 1 Kepanjen in the 2012/2013 academic year which consist of 31 students in each class. Cognitive learning outcome is measured by test items consist of four objective items and nine subjective items. Technique of data analysis in this research is two way ANOVA. Research results show that: (1) cognitive learning outcome and higher cognitive learning outcome of students in inquiry class is higher than students in LC 5E class; (2) cognitive learning outcome and higher cognitive learning outcome of students who have upper prior knowledge is higher than students who have lower prior knowledge in both inquiry and LC 5E.Key Words: learning outcome, inquiry, learning cycle 5E, solubility equilibria and the solubility product Abstrak: Penelitian ini bertujuan membandingkan keefektifan model inquiry dan LC 5E pada materi kelarutan dan hasil kali kelarutan untuk siswa dengan kemampuan awal berbeda. Keefektifan model pembelajaran dilihat dari hasil belajar kognitif siswa. Penelitian ini menggunakan rancangan eksperimen semu dengan desain faktorial 2x2. Subjek penelitian dipilih secara cluster random sampling yaitu dua kelas XI IPA SMAN 1 Kepanjen dengan jumlah masing-masing kelas sebanyak 31 siswa. Instrumen perlakuan yang digunakan adalah silabus dan RPP sedangkan instrumen pengukuran berupa soal tes terdiri dari empat soal objektif dan sembilan soal subjektif. Teknik analisis data menggunakan ANOVA dua jalur. Hasil penelitian yaitu (1) hasil belajar kognitif dan hasil belajar kognitif tingkat tinggi siswa yang dibelajarkan menggunakan model inquiry lebih tinggi dibandingkan model LC 5E; (2) hasil belajar kognitif dan hasil belajar kognitif tingkat tinggi siswa dengan kemampuan awal tinggi di kedua kelas eksperimen lebih tinggi daripada siswa dengan kemampuan awal rendah. Kata kunci: hasil belajar, inquiry, learning cycle 5E, kelarutan dan hasil kali kelarutan